MEMBANGUN USAHA DESA DENGAN DUNIA USAHA KOTA UNTUK MEMPERLUAS PASAR PRODUK LOKAL - Ngiw Aman Harja; Brilian Moktar (Jurnal Pengabdian Masyarakat Eka Prasetya, 2024)
The proposed solution is the development of a business network that connects village business actors with city business actors, through the use of technology and collaboration between the two parties. It is hoped that this solution can expand the market, increase product competitiveness, and encourage innovation in production and distribution. The aim of this program is to expand the market for local products, improve quality and competitiveness, and utilize technology for promotion and distribution, which will ultimately improve the village economy. The specific target of this program is to establish at least three business collaborations between village and city business actors as well as providing training related to digital marketing and branding techniques. The methods used include a participatory approach, digital marketing training, business networking facilitation, and mentoring to maximize product marketing.